(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Religious law refers to a set of moral and ethical principles that are promoted and obeyed byindividuals of various religious backgrounds and traditions all over the world. Examples of religions thatfollow religious law include Christianity, which bases its teachings on the Old Testament. The Shariah is akind of Hinduism that adheres to the lessons of the Vedas, the Dharma, and other holy books. Sikhism is asyncretistic religion that combines elements of Buddhism, Hinduism, Jainism, and others. The texts ofJainism provide a code of conduct for followers. Three Gunavratas (Subsidiary Vows) and four Siksavratas(Vows that instruct and lead one’s deeds) round up the five Oaths Vows of Anuvratas. Hate crimes andother forms of community violence have been frequent in India since since the country gained itsfreedom. Christians, Sikhs, and Muslims in India are all adversely affected by the country’s history ofreligiously motivated violence. This form of violence is typically employed for the purpose of gainingpower or influence in society or the economy. Mobs often react violently to these incidents, and in somecases governmental officials are directly involved, whether instigating violence through hate speech ordownplaying the importance of an in-depth inquiry into the events that had place.